Optic Pathway Tumors and Precocious Puberty - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The prevalence of precocious puberty and its relationship to optic pathway tumors (OPTs) have been examined in 219 children with neurofibromatosis 1 (NF-1) seen between Jan 1985 and April 1993 at Children's Memorial Hospital, Chicago.